Comparison of TPF and TP Induction Chemotherapy for Locally Advanced Nasopharyngeal Carcinoma Based on TNM Stage and Pretreatment Systemic Immune-Inflammation Index - Xiong, Ying; Shi, Liangliang; Zhu, Lisheng; Peng, Gang (Frontiers in Oncology, 2021)
Purpose To evaluate the efficacy and toxicity of the two IC (induction chemotherapy) regimens, TPF (taxanes, cisplatin, and 5-fluorouracil) and TP (taxanes and cisplatin) combined with concurrent chemoradiotherapy (CCRT) in locally advanced nasopharyngeal carcinoma (LA-NPC) patients. Methods Ultimately, we enrolled 213 patients at stage III-IVA in this retrospective study. The prognosis of TPF and TP was compared by Kaplan-Meier and Cox proportional hazard regression. The toxicities were evaluated according to CTCAE v4.0 and RTOG criteria. Results TPF was found to have a higher 5-year DMFS in stage IVA and N2-3 patients. The optimal value of pretreatment SII was 432.48. A further subgroup analysis revealed that patients in stage IVA combined with SII ≥432.48 showed superior OS (P=0.038) and DMFS (P=0.028) from TPF. Also, SII was proved to be a prognostic element for PFS (HR 2.801, P=0.018) and DMFS (HR 3.735, P=0.032) in multivariate analysis, and IC regimen (HR 2.182, P=0.049) for predicting DMFS. The rate of grade 3–4 leukopenia (P=0.038), neutropenia (P=0.021), radiation oral mucositis (P=0.048), diarrhea (P=0.036), and ear damage (P=0.046) were more common in TPF group. Conclusion Our study revealed that TPF regimen showed a higher 5-year DMFS for stage IVA and N2-3 patients, while for stage III and N0-1, TP might be ample. In high-risk LA-NPC patients (stage IVA combined with pretreatment SII ≥432.48), TPF had a higher 5-year OS and DMFS, with more grade 3–4 toxicities, but most of them were endurable.